Layered Double Hydroxide@Metal–Organic Framework Hybrids for Extraction of Indole-3-Carbinol From Cruciferous Vegetables - Tan, Qiyue; Liu, Guangyang; Zhao, Chenxi; Gao, Mingkun; Zhang, Xuan; Chen, Ge; Li, Lingyun; Huang, Xiaodong; Zhang, Yaowei; Lv, Jun; Xu, Donghui (Frontiers in Nutrition, 2022)
Cruciferous vegetables are rich in glucosinolates, which can be metabolized to produce the antitumor compound indole-3-carbinol (I3C). The conventional solvent extraction method for I3C is inefficient. To improve the extraction efficiency of I3C from cruciferous vegetables, we prepared a metal-organic framework (MOF) material (Fe3O4@Zn-Al-LDH@B-D-MIL-100). First, Fe3O4 nanoparticles were introduced to layered double hydroxides by in situ polymerization. Then, the MOF material was grown on the surface of the layered double hydroxide by co-precipitation and the layer-by-layer self-assembly method. This gave Fe3O4@Zn-Al-LDH@B-D-MIL-100, which was characterized using a variety of techniques. The results showed that Fe3O4@Zn-Al-LDH@B-D-MIL-100 had a double-layer porous structure, excellent superparamagnetism (11.54955 emu/g), a large specific surface area (174.04 m2/g), and a pore volume (0.26 cm3/g). The extraction conditions for I3C were optimized. Nonlinear fitting of the static adsorption model showed that the adsorption was mainly monolayer. Fe3O4@Zn-Al-LDH@B-D-MIL-100 had fast adsorption kinetics and could extract 95% of I3C in 45 min. These results are obviously superior to those of the traditional solvent extraction. The successful preparation of the new nanomaterial will provide a new reference for the enrichment and extraction of the I3C industry.